African biomass burning affects aerosol cycling over the Amazon - Bruna A. Holanda; Marco A. Franco; David Walter; Paulo Artaxo; Samara Carbone; Yafang Cheng; Sourangsu Chowdhury; Florian Ditas; Martin Gysel-Beer; Thomas Klimach; Leslie A. Kremper; Ovid O. Krüger; et al. (Communications Earth & Environment, 2023)
Abstract Smoke from vegetation fires affects air quality, atmospheric cycling, and the climate in the Amazon rain forest. A major unknown has remained the quantity of long-range transported smoke from Africa in relation to local and regional fire emissions. Here we quantify the abundance, seasonality, and properties of African smoke in central Amazonia. We show that it accounts for ~ 60% of the black carbon concentrations during the wet season and ~ 30% during the dry season. The African smoke influences aerosol-radiation interactions across the entire Amazon, with the strongest impact on the vulnerable eastern basin, a hot spot of climate and land use change. Our findings further suggest that the direct influence of African smoke has been historically relevant for soil fertilization, the carbon and water cycles, and, thus, the development of the Amazon forest ecosystem, even in the pre-industrial era.